PENGARUH PRAKTIK PERATAAN LABA PADA PERUSAHAAN TAMBANG YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ayu Kurnia Sari; Hendra Saputra; Wichita Ghekesia Nainggolan (Universitas Medan Area, 2019)
The aims of the research to know and analyze about whether the size of the company and profitability have a significant and partial or simultaneously effect on income smoothing practices. The typical data of research is secondary data with a quantitative approach. The population of this research were 12 mining companies which was listed in the Indonesia Stock Exchange from 2012-2016. The methodology of the the sample using census criteria, the total sample that was used 60 data. The analysis method used the classical assumption test, multiple linear regression, determination test, t test (partial test), and f test (simultaneous test). The results of this research shows that company size and profitability did not partially affect the practice of income smoothing. Meanwhile when it saw from simultaneoussize of the company and profitability have a significant effect on income smoothing practices (Case study of mining companies listed on the Indonesia Stock Exchange).